2009
DOI: 10.1186/1743-422x-6-128
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotypes/subgenotypes in voluntary blood donors in Makassar, South Sulawesi, Indonesia

Abstract: HBV/B and HBV/C are dominant in Makassar, similar to most areas in Indonesia. Mutations in BCP which might be associated with severity of liver disease are less common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
3
16
0
3
Order By: Relevance
“…The present study indicated that the distribution of three HBV genotypes (B, C, and D) and two predominant subgenotypes (C6 and D6) are nearly equal between the Austronesian language speakers and the Non‐Austronesian language speakers in the studied population, suggesting that the ancestors of Papuans was common to those of East Austronesian language speakers in the other regions in Indonesia. In support of this speculation, subgenotype D6 was found among the subjects in not only Papua, but also Makassar on Sulawesi Island [Utama et al, 2009; Utsumi et al, 2009; this study], whose ancestors are the East Austronesian language speakers. However, HBV strains of the two novel subgenotypes C11 and C12 were found only within the Non‐Austronesian language speakers in Namblong and Merauke.…”
Section: Discussionsupporting
confidence: 74%
“…The present study indicated that the distribution of three HBV genotypes (B, C, and D) and two predominant subgenotypes (C6 and D6) are nearly equal between the Austronesian language speakers and the Non‐Austronesian language speakers in the studied population, suggesting that the ancestors of Papuans was common to those of East Austronesian language speakers in the other regions in Indonesia. In support of this speculation, subgenotype D6 was found among the subjects in not only Papua, but also Makassar on Sulawesi Island [Utama et al, 2009; Utsumi et al, 2009; this study], whose ancestors are the East Austronesian language speakers. However, HBV strains of the two novel subgenotypes C11 and C12 were found only within the Non‐Austronesian language speakers in Namblong and Merauke.…”
Section: Discussionsupporting
confidence: 74%
“…It has been also reported from Morocco and Russia and Baltic region [57,58,74]. D6: It has been reported as a rare subgenotype from Indonesia, Kenya, Russia and Baltic region [22][23][24][25][26]54,55,74].…”
Section: Subgenotypes Of Genotype Dmentioning
confidence: 87%
“…However, genotype C and B are prevalent and D is rare (around 1%) in Eastern China and among genotype D, D1 and D2 are noted [10]. The subgenotype distribution of genotype D is also different among parts of India [24][25][26][27][28][29][30]. Similarly subgenotype studies may help tracking the movements of some population.…”
Section: Discussionmentioning
confidence: 99%
“…New subgenotypes, D5 to D7 were later described in India [28], Indonesia [29], and in the Mediterranean Basin [30], respectively.…”
Section: Introductionmentioning
confidence: 99%